(untitled) (Academia Journal of Medicine, 2021)
Background: To assess cases of COPD in known population. Subjects and Methods: Sixty- eight patients with COPD of both genders were enrolled in present study. History of smoking, type of cooking fuel combustion, family history, education level etc. was recorded. A thorough physical and clinical examination was performed in all patients. Results: Out of 68 COPD patients, male comprised 40 and female 28. Education was primary in 44, secondary in 10 and graduation in 2. BMI was underweight in 38, overweight in 12 and normal in 18 cases. Family history was positive in 40 and fuel used was LPG in 10, kerosene in 20 and wood in 38. A significant difference was observed (P< 0.05) [Table 2, Figure 1]. Conclusion: Chronic obstructive pulmonary disease is becoming common nowadays. Though underweight is one of the major cause but air pollution caused by combustion fuel cannot be overlooked.